2020
DOI: 10.1016/j.bbi.2020.04.077
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 presenting as stroke

Abstract: Acute stroke remains a medical emergency even during the COVID-19 pandemic. Most patients with COVID-19 infection present with constitutional and respiratory symptoms; while others present with atypical gastrointestinal, cardiovascular, or neurological manifestations. Here we present a series of four patients with COVID-19 that presented with acute stroke. Methods: We searched the hospital databases for patients that presented with acute stroke and concomitant features of suspected COVID-19 infection. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
505
3
20

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(564 citation statements)
references
References 17 publications
19
505
3
20
Order By: Relevance
“…A total sample of 8,771 participants was included in the systematic review. These studies were conducted in many countries worldwide including in China ( 13 , 40 , 43 ), France ( 37 , 39 , 48 , 50 ), India ( 42 ), Iran ( 51 ), Italy ( 32 , 33 , 46 ), the Netherlands ( 34 ), Philippines ( 52 ), Spain ( 44 , 53 ), Turkey ( 58 ), UK ( 41 , 55 ), and the USA ( 21 , 35 , 36 , 45 , 47 , 49 , 54 , 56 , 57 ). Out of 27 studies, eight studies were of retrospective cohort study design, 11 were case series, and nine were case reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total sample of 8,771 participants was included in the systematic review. These studies were conducted in many countries worldwide including in China ( 13 , 40 , 43 ), France ( 37 , 39 , 48 , 50 ), India ( 42 ), Iran ( 51 ), Italy ( 32 , 33 , 46 ), the Netherlands ( 34 ), Philippines ( 52 ), Spain ( 44 , 53 ), Turkey ( 58 ), UK ( 41 , 55 ), and the USA ( 21 , 35 , 36 , 45 , 47 , 49 , 54 , 56 , 57 ). Out of 27 studies, eight studies were of retrospective cohort study design, 11 were case series, and nine were case reports.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of stroke were almost equal for LVO (47 stroke cases in 10 studies) and non-LVO (42 cases in 10 studies). Location of LVOs involved were M1 vessels ( 21 , 37 , 41 , 42 , 44 , 45 , 47 , 53 , 54 ), M2 vessel ( 41 , 42 , 44 , 45 , 47 , 53 ), internal carotid ( 21 , 37 , 42 , 45 , 47 , 53 ), multiteritorial ( 37 , 47 ), posterior cerebral ( 41 , 45 ), basilar ( 37 ), ACA ( 21 , 53 ), and the vertebral artery ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recently conducted meta-analysis of 8-studies from China, including 46,248 infected patients showed that the most prevalent co-morbidities were hypertension (17%), diabetes mellitus (8%), followed by cardiovascular diseases (5%) 18,19 . In those reported cases without any vascular factors, the SARS-CoV-2 induced hypercoagulability may be the most important mechanism of the cerebrovascular disease 13,20 .…”
Section: Discussionmentioning
confidence: 83%
“…It is pertinent to add that there is recent literature describing acute ischemic stroke as being one of the presentations of COVID-19 infection. 2 Finally, we second the statement "better safe than sorry" in this hour of a COVID-19 pandemic.…”
Section: Distancementioning
confidence: 94%